Characterization and optimization of palm industry ash waste (PIAW) derived zeolites using central composite design (CCD) - Said, N.; Syafiqah, A. Khairuddin; Hajar Athirah, M. Sukri (2018)
The prodigious ashes from power electricity generation plants were devastated as solid waste by palm industries into environment. PIAW, mostly Palm Oil Fuel Ash (POFA) comprising silica and alumina was discarded as non-profit oriented products, thus this work aims to solve these issues by using ultrasound irradiation for PIAW derived zeolites synthesis. Pre-treated POFA as feedstock and formed zeolites were characterized and analyzed. CCD was employed for operation variables optimization. Alkaline concentration (0.6 M-1.4M), irradiation time (140 min-160 min) and KOH/POFA (1.5:1-2.5:1) were examined as non-constant variables. Otherwise, irradiation power (600W), temperature (80°C) and silica alumina ratio were justified as constant and response variables. An optimal synthesized zeolites as ratio of SiO2 and Al2O3 (10.60) was found from surface plot based on quadratic typical at KOH=1 M, KOH/POFA=2 and time=150 min. Presence of A, P, X and irregular shape structures zeolites are commensurable to another resources, mainly fly ash.